2017
DOI: 10.1038/ejhg.2017.40
|View full text |Cite
|
Sign up to set email alerts
|

From older to younger: intergenerational promotion of health behaviours in Portuguese families affected by familial amyloid polyneuropathy

Abstract: The role of older generations in families with hereditary diseases has been recognised and associated to their function as guardians of the family's medical history. However, research is scarce in examining the roles that older generations play in terms of health promotion and risk management towards younger generations, which is particularly evident with incurable genetically inherited disorders such as familial amyloid polyneuropathy (FAP) ATTR Val30Met. This qualitative exploratory study examines the roles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
0
14
0
3
Order By: Relevance
“…Open communication www.FamilyProcess.org 840 / FAMILY PROCESS allows family members to develop a shared understanding and support one another, becoming more likely to cope and adapt well to living with the genetic condition or its risk and establishing more resilient relations (Hoskins, Roy, Peters, Loud, & Greene, 2008). Open communication tends to occur more frequently among women, first-degree relatives, or spouses (Oliveira, Mendes, & Sousa, 2017), while those under 18 years are less likely to be given information (Van Oostrom et al, 2007). Approximately 40% of parents do not talk to their children about their family's condition, although most would like to be able to do so (Metcalfe, Coad, Plumridge, Gill, & Farndon, 2008).…”
Section: Rita's Guilt: Gathering Extended Family Members For Predictimentioning
confidence: 99%
“…Open communication www.FamilyProcess.org 840 / FAMILY PROCESS allows family members to develop a shared understanding and support one another, becoming more likely to cope and adapt well to living with the genetic condition or its risk and establishing more resilient relations (Hoskins, Roy, Peters, Loud, & Greene, 2008). Open communication tends to occur more frequently among women, first-degree relatives, or spouses (Oliveira, Mendes, & Sousa, 2017), while those under 18 years are less likely to be given information (Van Oostrom et al, 2007). Approximately 40% of parents do not talk to their children about their family's condition, although most would like to be able to do so (Metcalfe, Coad, Plumridge, Gill, & Farndon, 2008).…”
Section: Rita's Guilt: Gathering Extended Family Members For Predictimentioning
confidence: 99%
“…When a disease is recognized for several generations, an acquired “pattern” of transgenerational family structuring may occur and be determinant, less pathologic and more adaptive. In fact, an intergenerational flow of support and promotion of healthy behaviors across generations were described by Oliveira et al This intergenerational knowledge, along with a connected functioning in those families may act as a protective factor, contributing to more balanced results.…”
Section: Discussionmentioning
confidence: 99%
“…20 A study of Portuguese TTR-FAP Val30Met patients on transgenerational aspects of the illness to understand the role of older generations has shown that there was an intergenerational flow of support, and that communication was higher among affected members and between mothers and affected daughters. 21 The aims of this study were to (1) evaluate how TTR-FAP Val30-Met affected patients and pre-symptomatic carriers perceive their family´s functioning, (2) compare the perception of the family system by these two groups to that of their partners, and (3) compare the above mentioned perceptions to those of patients with multiple sclerosis (MS).…”
Section: Livermentioning
confidence: 99%
See 1 more Smart Citation
“…This exploratory, qualitative study was drawn from a larger empirical study examining processes of communication of information about genetic risks in families affected by LONDs, including familial amyloid polyneuropathy TTR Val30Met, HD and MJD [22][23][24]. We present here the subcorpus of data focusing on decisions of non-engagement with PST, a relevant theme that emerged during that analysis, drawing on data from families with MJD (the majority in that study).…”
Section: Methodsmentioning
confidence: 99%